Positive electrode composite material, method for manufacturing positive electrode composite material, and lithium ion battery
By mechanically mixing and heating treatment in the sulfur-based positive electrode composite material, a positive electrode composite material with characteristic crystallinity is generated, which solves the problem of high ion resistance in the prior art and significantly improves the performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202380054930.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-10
- Filing Date
- 2023-08-02
- Publication Date
- 2025-03-14
AI Technical Summary
In the prior art, there is still room for improvement in the ion resistance of sulfur-based positive electrode composite materials, which affects the performance of lithium-ion batteries.
By mechanically mixing the sulfur-based active substance with a solid electrolyte and heating treatment under specific temperature conditions, a positive electrode composite material with characteristic crystallinity is generated. The material exhibits specific diffraction peaks A and B in powder X-ray diffraction of CuKα rays, and the conductive additive contains pores with a pore size less than 5 nm.
It effectively reduces the ion resistance of the positive electrode composite material and improves the performance of lithium-ion batteries.
Smart Images

Figure BDA0005249543180000121 
Figure BDA0005249543180000131 
Figure HDA0005249543190000011
Abstract
Description
Technical Field
[0001] The invention relates to a positive electrode composite material, a method for producing the positive electrode composite material and a lithium ion battery.
[0002] Specifically, the present invention relates to a positive electrode composite material capable of reducing ionic resistance, a method for producing the positive electrode composite material, and a lithium ion battery. Background Art
[0003] In sulfur-based positive electrode composite materials used in lithium ion batteries and the like, sulfur is composited with a conductive additive and a solid electrolyte, so that the insulating sulfur reaction can be sufficiently caused (Patent Documents 1 to 3).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2014-011033
[0007] Patent Document 2: Japanese Patent Application Publication No. 2020-161288
[0008] Patent Document 3: International Publication No. 2022 / 080435 Summary of the invention
[0009] However, from the viewpoint of reducing the ionic resistance of the positive electrode composite material, it has been found that the prior art including Patent Documents 1 to 3 still has room for further improvement.
[0010] One of the objects of the present invention is to provide a positive electrode composite material capable of reducing ionic resistance, a method for producing the positive electrode composite material, and a lithium ion battery.
[0011] The present inventors have conducted intensive studies and found that a positive electrode composite material satisfying specific conditions can reduce ion resistance, thereby completing the present invention.
[0012] According to the present invention, the following positive electrode composite material and the like can be provided.
[0013] 1. A positive electrode composite material comprising a sulfur active material and a solid electrolyte,
[0014] In powder X-ray diffraction using CuKα rays, there is a diffraction peak A at 2θ=25.6±0.5° and a diffraction peak B at 2θ=45.2±1.0°.
[0015] The half width of the diffraction peak A is greater than 0.25°.
[0016] 2. The positive electrode composite material as described in 1, wherein the left-right asymmetry parameter ε' of the diffraction peak B is 1.50×104 above.
[0017] 3. The positive electrode composite material as described in 1 or 2, further comprising a conductive auxiliary agent.
[0018] 4. The positive electrode composite material as described in 3, wherein the conductive auxiliary agent has pores with a pore diameter of less than 5 nm.
[0019] 5. The positive electrode composite material according to 3 or 4, wherein the conductive auxiliary agent includes one or more selected from the group consisting of activated carbon and carbon black.
[0020] 6. The positive electrode composite material as described in any one of items 1 to 5 is obtained by heating a positive electrode composite material precursor obtained by mechanically mixing a sulfur-based active material and a solid electrolyte, wherein the solid electrolyte has a diffraction peak A at 2θ=25.6±0.5° and a diffraction peak B at 2θ=45.2±1.0° in powder X-ray diffraction using CuKα rays.
[0021] 7. The positive electrode composite material as described in 6, wherein the temperature of the heating treatment is 160 to 280°C.
[0022] 8. A method for manufacturing a positive electrode composite material, comprising:
[0023] A positive electrode composite material precursor is obtained by mechanically mixing a sulfur-based active material with a solid electrolyte, wherein the solid electrolyte has a diffraction peak A at 2θ=25.6±0.5° and a diffraction peak B at 2θ=45.2±1.0° in powder X-ray diffraction using CuKα rays; and
[0024] The positive electrode composite material precursor is subjected to a heating treatment to obtain a positive electrode composite material,
[0025] The temperature of the heating treatment is 160-280°C.
[0026] 9. A lithium ion battery comprising the positive electrode composite material according to any one of 1 to 7.
[0027] According to the present invention, a positive electrode composite material capable of reducing ion resistance, a method for producing the positive electrode composite material, and a lithium ion battery can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a graph showing the results of powder X-ray diffraction (XRD).
[0029] Figure 2 yes Figure 1 A magnified view of the high-angle side of the XRD.
[0030] Figure 3This is a diagram showing the XRD results of Example 3. DETAILED DESCRIPTION
[0031] Hereinafter, the cathode composite material, the method for producing the cathode composite material, and the lithium ion battery of the present invention will be described in detail.
[0032] In addition, in this specification, "x to y" is a numerical range indicating "x or more and y or less." Regarding the numerical range, the upper limit value and the lower limit value described can be arbitrarily combined.
[0033] 1. Positive electrode composite materials
[0034] A positive electrode composite material of one embodiment of the present invention comprises a sulfur-based active material and a solid electrolyte, and has a diffraction peak A at 2θ=25.6±0.5° and a diffraction peak B at 2θ=45.2±1.0° in powder X-ray diffraction using CuKα rays, and the half width of the diffraction peak A is greater than 0.25°.
[0035] According to the positive electrode composite material of this embodiment, the effect of reducing ion resistance can be obtained.
[0036] The positive electrode composite material of this proposal cannot be produced by existing technology.
[0037] That is, when a method of adding a solid electrolyte to a sulfur-carbon complex and applying strong energy to mechanically mix the solid electrolyte is used, the crystallinity of the solid electrolyte is reduced due to the mechanical mixing, and Li + The electrical conductivity decreases, and therefore the ionic resistance increases.
[0038] In contrast, by heat treatment at a specific temperature condition (described later in detail) after mechanical mixing, the solid electrolyte can be given characteristic crystallinity that contributes to the reduction of ionic resistance. In addition to the original crystal phase, a new crystal phase with a slightly different lattice constant is generated, and as a result, such crystallinity can be given. Due to the presence of these crystal phases, the half width of the above-mentioned diffraction peak A is greater than 0.25°, and in addition, it is preferred that the left-right asymmetry parameter ε' of the diffraction peak B described later is 1.50×10 4 above.
[0039] Powder X-ray diffraction using CuKα rays was performed by the method described in Examples.
[0040] The half width of the diffraction peak A is a value obtained by subtracting a device constant, and is specifically calculated by the method described in Examples.
[0041] In one embodiment, the half width of the diffraction peak A is 0.25° or more, 0.26° or more, 0.27° or more, 0.28° or more, 0.29° or more, 0.30° or more, 0.31° or more, or 0.32° or more. The upper limit is not particularly limited, for example, 2.0° or less.
[0042] In one embodiment, the left-right asymmetry parameter ε' of the diffraction peak B is 1.50×10 4 As a result, the effect of the present invention is more significantly exerted.
[0043] The left-right asymmetry parameter ε' of the diffraction peak B was calculated by the method described in Examples.
[0044] In one embodiment, the left-right asymmetry parameter ε' of the diffraction peak B is 1.50×10 4 Above, 2.00×10 4 Above, 3.00×10 4 Above, 4.00×10 4 Above, or 5.00×10 4 The upper limit is not particularly limited, but is, for example, 5.00×10 5 the following.
[0045] The sulfur-based active material is not particularly limited, and examples thereof include sulfur, lithium sulfide (Li 2 S), lithium polysulfide (Li 2 S n :n satisfies 1<n≤8)、titanium sulfide (TiS 2 ), molybdenum sulfide (MoS 2 ), iron sulfide (FeS, FeS 2 ), copper sulfide (CuS), nickel sulfide (Ni 3 S 2 ), sulfur-containing polymer compounds, etc.
[0046] The sulfur is not particularly limited, but is preferably high-purity sulfur. Specifically, the purity is preferably 95% by mass or more, more preferably 96% by mass or more, and particularly preferably 97% by mass or more.
[0047] Examples of the crystal system of sulfur include α sulfur (orthorhombic system), β (monoclinic system), γ (monoclinic system), and amorphous sulfur, etc. These may be used alone or in combination of two or more.
[0048] The positive electrode composite material can contain, as a solid electrolyte, a solid electrolyte having a diffraction peak A at 2θ=25.6±0.5° and a diffraction peak B at 2θ=45.2±1.0° in powder X-ray diffraction using CuKα rays.
[0049] As such a solid electrolyte, a solid electrolyte having an argyrodite-type crystal structure can be exemplified. As the argyrodite-type crystal structure, for example, Li 7 PS 6 Crystal structure; with Li 7 PS 6 The structural skeleton is composed of the formula Li 7- x P 1-y Si y S 6 Li 7+x P 1-y Si y S 6 (x is -0.6 to 0.6, y is 0.1 to 0.6) represented by the crystal structure; 7-x-2y PS 6-x- y C l x The crystal structure represented by (0.8≤x≤1.7, 0<y≤-0.25x+0.5); 7-x PS 6-x Ha x (Ha is Cl or Br, and x is preferably 0.2 to 1.8)
[0050] However, the solid electrolyte containing the above-mentioned argyrodite type crystal structure alone as the crystal structure, and the positive electrode composite material containing the solid electrolyte and mechanically mixed, do not satisfy the condition that the half width of the diffraction peak A is 0.25° or more, nor that the left-right asymmetry parameter ε' of the diffraction peak B is 1.50×10 4 As described above, by performing a heat treatment under specific temperature conditions after mechanical mixing, a new crystal phase is generated at a slightly deviated position in addition to the original crystal phase, and as a result, these conditions are satisfied.
[0051] (Conductive additive)
[0052] In one embodiment, the positive electrode composite material further includes a conductive additive.
[0053] In one embodiment, the conductive aid is a carbon material.
[0054] The conductive aid as a carbon material can be any material with electronic conductivity. The conductive aid preferably has a plurality of pores. A carbon material with pores is particularly preferred. Carbon materials have high conductivity and are lighter than other conductive materials, so the output density and capacity per unit weight of the battery can be increased.
[0055] The specific surface area of the conductive additive is preferably 0.1 m 2 / g above 5000m2 / g or less, more preferably 1m 2 / g above 4000m 2 / g or less, more preferably 1m 2 / g above 3000m 2 / g or less, and most preferably 10m 2 / g above 3000m 2 / g or less.
[0056] The pore volume of the conductive auxiliary agent is preferably 0.1 cc / g to 5.0 cc / g.
[0057] The average diameter of the pores of the conductive auxiliary agent is preferably 0.1 nm to 40 nm, more preferably 0.5 nm to 40 nm, further preferably 0.5 nm to 20 nm, and most preferably 1 nm to 20 nm.
[0058] The specific surface area, pore volume and pore diameter of the conductive auxiliary agent can be obtained by using a nitrogen adsorption isotherm obtained by adsorbing nitrogen gas on the conductive auxiliary agent at a liquid nitrogen temperature. Specifically, the specific surface area can be calculated by the Brenauer-Emmet-Telle (BET) multi-point method using the nitrogen adsorption isotherm. In addition, the pore volume and pore diameter can be obtained by the Barret-Joyner-Halenda (BJH) method using the nitrogen adsorption isotherm.
[0059] As a measuring device, for example, a specific surface area and pore size distribution measuring device (Autosorb-3) manufactured by Quantachrome Technologies Inc. can be used for measurement.
[0060] As carbon material, there is no particular limitation, and examples thereof include carbon black such as Ketjen black, acetylene black, superconducting acetylene black (Denka Black), thermal black, channel black, mesoporous carbon, activated carbon, amorphous carbon, carbon nanotubes, vapor grown carbon fiber (VGCF), carbon nanohorns, fullerenes, carbon fiber, natural graphite, artificial graphite, graphene, graphene oxide, reduced graphene oxide, etc. In addition, these can be used alone, or two or more can be used in combination. In addition, these composite materials can also be used.
[0061] Mesoporous carbon is a carbon material having two-dimensional or three-dimensional pores, which can be obtained by the preparation methods described in the following literature: for example, S. J. Song, S. H. Joo, R. Ryoo, etc., J. Am. Chem. Soc. (Journal of the American Chemical Society), 122 (2000) 10712-10713, and T. Yokoi, Y. Sakamoto, O. Terasaki, etc., J. Am. Chem. Soc. (Journal of the American Chemical Society), 128 (2006) 13664-13665.
[0062] In one embodiment, the conductive auxiliary agent has pores with a pore diameter of less than 5 nm.
[0063] In one embodiment, the conductive auxiliary agent does not have pores having a pore diameter of 5 nm or more.
[0064] In addition, the pore diameter is a value measured by a nitrogen adsorption-desorption measurement method.
[0065] In one embodiment, the conductive auxiliary agent includes one or more selected from the group consisting of activated carbon and carbon black.
[0066] In one embodiment, the conductive auxiliary agent does not include "a carbon replica having a three-dimensional honeycomb structure (closed-cell structure) and having pores with a pore diameter of 5 nm to 20 nm".
[0067] In one embodiment, the positive electrode composite material may or may not contain other components besides the sulfur-based active material, the solid electrolyte and the conductive additive.
[0068] The other components are not particularly limited, and examples thereof include a binder, a solvent, and a dispersant.
[0069] In the positive electrode composite material, the contents of the sulfur-based active material, the solid electrolyte, and the conductive aid are not particularly limited.
[0070] In one embodiment, the content of the sulfur-based active material is 40 to 350 parts by mass based on 100 parts by mass of the solid electrolyte.
[0071] When the positive electrode composite material contains a conductive auxiliary agent, the mass ratio of the sulfur-based active material to the conductive auxiliary agent (sulfur-based active material:conductive auxiliary agent) is 10:90 to 95:5, preferably 30 to 70:90 to 10.
[0072] In one embodiment, 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, 99% by mass or more, 99.5% by mass or more, or substantially 100% by mass of the positive electrode composite material is a sulfur-based active material and a solid electrolyte, or a sulfur-based active material, a solid electrolyte, and a conductive aid. In addition, in the case of "substantially 100% by mass", unavoidable impurities may also be included.
[0073] In one embodiment, the positive electrode composite material is obtained by heating a positive electrode composite material precursor obtained by mechanically mixing a sulfur-based active material with a solid electrolyte, wherein the solid electrolyte has a diffraction peak A at 2θ=25.6±0.5° and a diffraction peak B at 2θ=45.2±1.0° in powder X-ray diffraction using CuKα rays.
[0074] In one embodiment, the temperature of the heat treatment is 160-280°C.
[0075] Regarding these embodiments, the following description of the method for producing a positive electrode composite material according to one aspect of the present invention is cited.
[0076] 2. Method for manufacturing positive electrode composite material
[0077] A method for manufacturing a positive electrode composite material according to one embodiment of the present invention comprises: obtaining a positive electrode composite material precursor by mechanically mixing a sulfur-based active material with a solid electrolyte, wherein the solid electrolyte has a diffraction peak A at 2θ=25.6±0.5° and a diffraction peak B at 2θ=45.2±1.0° in powder X-ray diffraction using CuKα rays; and obtaining a positive electrode composite material by heat-treating the positive electrode composite material precursor, wherein the heating treatment temperature is 160 to 280°C.
[0078] According to the method for producing a cathode composite material of this embodiment, the ion resistance of the obtained cathode composite material can be reduced.
[0079] That is, by heat treating at a specific temperature of 160 to 280° C. after mechanical mixing, the solid electrolyte can be given characteristic crystallinity that contributes to the reduction of ionic resistance. In addition to the original crystal phase, a new crystal phase with a slightly different lattice constant is generated, and as a result, such crystallinity can be given. In this way, the positive electrode composite material of one embodiment of the present invention can be manufactured.
[0080] When the temperature of the heat treatment is lower than 160° C., the formation of a new crystal phase is insufficient, and the reduction of the ionic resistance is insufficient.
[0081] When the temperature of the heat treatment exceeds 280° C., the original crystal phase decomposes and an impurity phase (2θ=29°) is generated, making the material unsuitable as a positive electrode composite material.
[0082] Examples of the mixing device used for mechanical mixing include a planetary ball mill, a tumbling mill, a bead mill, a FILMIX (thin film gyratory high-speed mixer), a NAUTA mixer (conical screw mixer), a cyclone mixer, a twin-shaft extruder, a multi-shaft roll, and a solid phase shear kneader.
[0083] In one embodiment, the temperature of the heat treatment can be above 160°C, above 165°C, above 170°C, above 175°C, above 180°C or above 185°C, and can be below 280°C, below 270°C, below 260°C, below 250°C, below 240°C, below 230°C, below 220°C, below 215°C, below 210°C, below 205°C, below 200°C or below 195°C.
[0084] From the viewpoint of more significantly reducing the ionic resistance of the positive electrode composite material, the temperature of the heat treatment is preferably close to 190° C. within the above range.
[0085] In the above description of the temperature of the heat treatment, "X°C or less" means that heating is not performed at a temperature exceeding X°C.
[0086] The time of the heat treatment is not particularly limited, but preferably the heating is performed within the above temperature range for 30 minutes or longer, 60 minutes or longer, or 90 minutes or longer. The upper limit is not particularly limited, but is, for example, 20 hours or shorter or 10 hours or shorter.
[0087] As the sulfur-based active material, the sulfur-based active material described in the positive electrode composite material according to one embodiment of the present invention can be used.
[0088] As the solid electrolyte, a solid electrolyte having a diffraction peak A at 2θ=25.6±0.5° and a diffraction peak B at 2θ=45.2±1.0° in powder X-ray diffraction using CuKα rays is used. As such a solid electrolyte, a solid electrolyte having an argyrodite-type crystal structure described in the positive electrode composite material of one embodiment of the present invention can be cited.
[0089] The method for producing a solid electrolyte having an argyrodite-type crystal structure is not particularly limited, and a known method can be used. The raw material mixture is more preferably a combination of lithium sulfide, phosphorus sulfide, and lithium halide, and more preferably Li 2 S.P. 2 S 5 and combinations of LiCl and / or LiBr.
[0090] For example, when using Li 2 S.P. 2 S 5 When LiCl and LiBr are used as raw materials for the argyrodite-type solid electrolyte, the molar ratio of the raw materials can be set to Li 2 S:P 2 S 5 : The total of LiCl and LiBr = 30-60: 10-25: 15-50.
[0091] The solid electrolyte containing the argyrodite type crystal structure can be manufactured by fully mixing the above raw material mixture using, for example, a mortar, a ball mill, a vibration mill, a rolling mill, or a kneader and then heat-treating it. From the aspect of being able to continuously process in a short time, it is preferred to use a kneader for mixing. The kneader is not particularly limited, and is preferably a multi-axis kneader having two or more axes. In this mixing, the raw material mixture can also be reacted to form glass.
[0092] The heat treatment temperature is preferably 350 to 480°C, more preferably 360 to 460°C, and particularly preferably 380 to 450°C.
[0093] The heat treatment time varies depending on the composition and temperature, and may be adjusted within a range of, for example, 10 minutes to 48 hours.
[0094] The atmosphere of the heat treatment is not particularly limited, but is preferably an atmosphere of an inert gas such as nitrogen or argon, rather than a hydrogen sulfide gas flow.
[0095] The shape of the solid electrolyte is not particularly limited, and may be, for example, a particle shape. The average particle size (D 50 ) and the average particle size (D 50 ) Similarly, for example, it can be exemplified within the range of 0.01 μm to 500 μm and 0.1 to 200 μm.
[0096] In one embodiment, the sulfur-based active material to be subjected to mechanical mixing is preliminarily composited with a conductive auxiliary agent. As the conductive auxiliary agent, the conductive auxiliary agent described in the positive electrode composite material according to one embodiment of the present invention can be used.
[0097] For example, the sulfur-based active material and the conductive auxiliary agent can be composited by heating them together before mechanical mixing. The heating temperature is not particularly limited, and is, for example, 120 to 350°C.
[0098] The mass ratio of the sulfur-based active material to the conductive auxiliary agent (sulfur-based active material:conductive auxiliary agent) is 10:90 to 95:5, preferably 30:70 to 90:10.
[0099] In one embodiment, the positive electrode composite material produced by the method for producing a positive electrode composite material according to this embodiment is the positive electrode composite material according to one embodiment of the present invention described above.
[0100] 3. Lithium-ion battery
[0101] A lithium ion battery according to one embodiment of the present invention includes the positive electrode composite material according to one embodiment of the present invention described above.
[0102] According to the lithium ion battery of this embodiment, the ion resistance of the positive electrode composite material can be reduced, so that the effect of being able to operate at low resistance can be obtained.
[0103] The positive electrode composite material can be used as a positive electrode layer of a lithium ion battery. In this case, other structures of the lithium ion battery can use structures known in the technical field, and a negative electrode layer containing no lithium ions in the negative electrode active material can be selected.
[0104] In addition, the negative electrode active material contained in the negative electrode layer of the lithium ion battery can be referred to as “negative electrode active material containing lithium ions”. In addition, the negative electrode active material contained in the negative electrode layer of the lithium ion battery can also be “negative electrode active material that supplies lithium ions to the positive electrode”.
[0105] The negative electrode of the lithium ion battery is not particularly limited as long as it can be used in a common battery. The negative electrode may be composed of a negative electrode mixture obtained by mixing a negative electrode active material and a solid electrolyte.
[0106] As the negative electrode active material, commercially available materials can be used. For example, carbon materials, Sn metal, In metal, Si metal, alloys of these metals, etc. can be used. Specifically, natural graphite or various graphites; metal powders of Si, Sn, Al, Sb, Zn, Bi, etc.; SiAl, Sn 5 Cu 6 Sn 2 Co、Sn 2 Metal alloys such as Fe; other amorphous alloys or plated alloys. There is no particular limitation on the particle size, and those with an average particle size of several μm to 80 μm can be suitably used.
[0107] The electrolyte layer is not particularly limited, and a known electrolyte layer can be used. For example, preferably an oxide solid electrolyte, a sulfide solid electrolyte, a polymer electrolyte, and from the viewpoint of ionic conductivity, more preferably a sulfide solid electrolyte. The sulfide solid electrolyte is preferably an electrolyte for the above-mentioned cathode composite material.
[0108] The method for manufacturing a lithium-ion battery is not particularly limited. For example, the following method can be cited: a positive electrode layer composed of a positive electrode composite material according to one embodiment of the present invention is formed on a positive electrode collector to form a sheet, a solid electrolyte layer is formed on the sheet, and a sheet having a negative electrode layer formed on a negative electrode collector is stacked and pressed.
[0109] Example
[0110] Examples of the present invention will be described below, but the present invention is not limited to these examples.
[0111] 1. Manufacturing of positive electrode composite materials
[0112] (Example 1)
[0113] (1) Preparation of composite powder A
[0114] Activated carbon (MSC-30 manufactured by Kansai Thermochemical Co., Ltd.) and sulfur were placed in a glass bottle at a weight ratio of 3:7, and then sealed in a SUS tube container. The activated carbon and sulfur composite powder A was obtained by heating at 150°C for 6 hours and at 300°C for 2.75 hours in an electric furnace.
[0115] (2) Preparation of solid electrolyte
[0116] 0.4129 g of lithium sulfide, 0.5875 g of phosphorus pentasulfide, 0.2241 g of lithium chloride, 0.2755 g of lithium bromide, and 10 zirconia balls with a diameter of 10 mm were placed in a 45 ml zirconia can and sealed. A planetary ball mill (FRITSCH, model P-7) was used to mix (mechanically grind) at a speed of 370 rpm for 60 hours to obtain a powder. The obtained powder was heated at 430°C for 8 hours to obtain a solid electrolyte A.
[0117] (3) Preparation of positive electrode composite material powder
[0118] 0.45g of composite powder A and 0.45g of solid electrolyte A were put into a 45ml zirconia can together with 10 zirconia balls with a diameter of 10mm, and sealed. A planetary ball mill device (FRITSCH, model P-7) was used to mix at a speed of 370rpm, a time of 20h, and room temperature to obtain composite powder B (positive electrode composite material precursor). The obtained composite powder B was heated at 190°C for 2 hours to obtain a positive electrode composite material.
[0119] (Example 2)
[0120] A positive electrode composite material was obtained by the same procedure as in Example 1 except that the heating temperature of the composite powder B was changed to 160°C.
[0121] (Example 3)
[0122] A positive electrode composite material was obtained by the same procedure as in Example 1 except that the heating temperature of the composite powder B was changed to 200°C.
[0123] (Example 4)
[0124] A positive electrode composite material was obtained by the same procedure as in Example 1 except that the heating temperature of the composite powder B was changed to 220°C.
[0125] (Comparative Example 1)
[0126] A positive electrode composite material was obtained by the same procedure as in Example 1 except that the heating of the composite powder B was omitted.
[0127] (Comparative Example 2)
[0128] A positive electrode composite material was obtained by the same procedure as in Example 1 except that the heating conditions of the composite powder B were changed to heating at 150° C. for 6 hours and then heating at 300° C. for 2 hours and 45 minutes.
[0129] 2. Measurement and evaluation methods
[0130] (1) Powder X-ray diffraction of positive electrode composite powder
[0131] The obtained positive electrode composite material powder was measured by XRD measurement.
[0132] The positive electrode composite material powder of each example was filled into a groove with a diameter of 20 mm and a depth of 0.2 mm, and the sample was made by flattening with glass. The sample was sealed with a kapton film for XRD and measured in a way that it was not in contact with air. In addition, as a reference ( Figure 1 , 2 ), the solid electrolyte A and the composite powder A were mixed in a mortar at 0.45 g each in a manner that did not impair the crystallinity of the solid electrolyte A. As a result, peaks derived from the argyrodite type crystal structure were observed at 2θ=25.6°, 30.2°, 45.2°, etc. in the XRD pattern.
[0133] The measurement was performed using a powder X-ray diffraction measuring apparatus D2PHASER manufactured by Bruker Corporation under the following conditions.
[0134] Tube voltage: 30kV
[0135] Tube current: 10mA
[0136] ·X-ray wavelength: Cu-Kα ray
[0137] Optical system: Concentration method
[0138] Slit structure: Soller slit 4° (same for incident and receiving sides), divergence slit 1mm, Kβ filter (Ni plate 0.5%), air scattering screen (3mm)
[0139] Detector: Semiconductor detector
[0140] Measuring range: 2θ=10-60°
[0141] Step width, scanning speed: 0.05°, 0.05° / sec
[0142] In addition, regarding the X-ray diffraction pattern, the presence or absence of the diffraction peak A at 2θ=25.6±0.5° and the diffraction peak B at 2θ=45.2±1.0° were determined by the following method. Furthermore, the half width of the diffraction peak A was determined by the following method.
[0143] Method for determining whether diffraction peak A and diffraction peak B exist
[0144] Diffraction peak A
[0145] Regarding whether there is a diffraction peak A in the range of 2θ = 25.6 ± 0.5°, in the X-ray diffraction pattern, the average value of the X-ray intensity (counts) at 2θ = (25.6-0.5) ± 0.2°, i.e., 2θ = 25.1 ± 0.2°, and 2θ = (25.6 + 0.5) ± 0.2°, i.e., 2θ = 26.1 ± 0.2° is set as the intensity I of the background (BG). bg The maximum value of the X-ray intensity (counts) at 2θ = 25.1 ± 0.5° is set as the peak intensity I peak When the ratio (I peak / I bg ) is 1.200 or more, it is determined that diffraction peak A exists.
[0146] The ratio of diffraction peak A (I peak / I bg ) is preferably 1.250 or more, more preferably 1.300 or more.
[0147] Diffraction peak B
[0148] Regarding whether there is a diffraction peak B in the range of 2θ = 45.2 ± 1.0°, in the X-ray diffraction pattern, the average value of the X-ray intensity (counts) at 2θ = (45.2-1.0) ± 0.2°, i.e., 2θ = 44.2 ± 0.2°, and 2θ = (45.2 + 1.0) ± 0.2°, i.e., 2θ = 46.2 ± 0.2° is set as the intensity I of the background (BG). bg The maximum value of the X-ray intensity (counts) at 2θ = 45.2 ± 1.0° is set as the peak intensity I peak When the ratio (I peak / I bg ) is 1.250 or more, it is determined that diffraction peak B exists.
[0149] The ratio of diffraction peak B (I peak / I bg ) is preferably 1.300 or more, more preferably 1.350 or more.
[0150] The above results show that, in the positive electrode composite materials of Examples 1 to 4 and Comparative Example 1, the ratio (I peak / I bg ) are 2.578, 2.629, 2.704, 2.838, 2.311 respectively, and the diffraction peak A is judged to be "existent". peak / I bg ) are 3.287, 3.232, 3.370, 3.370, and 2.688, and the diffraction peak B is judged to be "existent".
[0151] On the other hand, in the positive electrode composite material of Comparative Example 2, the ratio (I peak / I bg ) is 1.108 and the diffraction peak A is judged to be "non-existent". peak / I bg ) is 1.198 and the diffraction peak B is judged to be “non-existent”.
[0152] Calculation of half width
[0153] The half width β from which the device constant is subtracted is calculated according to β=wB.
[0154] w: half width of the peak (diffraction peak A) at 25.6±0.5° obtained by measurement
[0155] B: Device constant (B = 0.1269° was obtained from the peak at 2θ = 28.4° by measuring the standard substance (silicon) in the same way)
[0156] w (the half width obtained by measurement) is obtained as follows. A straight line baseline is set on the peak shape obtained by XRD measurement, and the difference between the intensity of each point and the baseline is taken to form an XRD curve. The XRD curve is set as a formula composed of the Lorentz function L(x) and the Gaussian function G(x) (f(x) = (1-α) × L(x) + α × G(x)), and the parameters A (corrected peak intensity), w, and x are determined by curve fitting. 0 (2θ of the peak top) and α (ratio of the Lorentzian function).
[0157] [Number 1]
[0158]
[0159] In curve fitting, the range of about ±1.0° from the peak is appropriately set as the fitting range. The error between the intensity of the fitting curve calculated by f(x) at each θ and the intensity of the XRD curve is taken, and the value obtained by adding the errors of the entire fitting range is minimized to perform fitting. The solver function (GRG nonlinear) of spreadsheet software (Excel, Microsoft) is used here.
[0160] Left-right asymmetry parameter ε'
[0161] The peak at 2θ=45.2±1.0° (diffraction peak B) is processed in the same manner as in the above-mentioned "(3) Calculation of half width of powder X-ray diffraction", and a baseline-corrected XRD curve and a fitting curve f(x) (44.38°≤θ≤46.05°) are obtained. In addition, f(x) is a left-right symmetrical curve fitted in a manner that minimizes the error ε with the XRD curve, i.e., the sum of the squares of the intensity differences at each θ. At this time, if the error rate ε' is defined as follows, it can be said that the larger the ε', the greater the error when fitting with a left-right symmetrical curve, that is, the higher the left-right asymmetry of the peak.
[0162] ε' = total error / number of elements (number of plots at 44.38°≤θ≤46.05°)
[0163] (2) Evaluation of ionic resistance
[0164] Preparation of solid electrolyte
[0165] 0.4127 g of lithium sulfide, 0.6655 g of phosphorus pentasulfide, 0.2137 g of lithium iodide, 0.2080 g of lithium bromide, and 10 zirconia balls with a diameter of 10 mm were placed in a 45 ml zirconia can and sealed. A planetary ball mill (FRITSCH, model P-7) was used to mix (mechanically grind) at a speed of 370 rpm for 40 hours to obtain a powder. The obtained powder was heated at 195°C for 3 hours to obtain a solid electrolyte B.
[0166] Fabrication of ionic resistance measurement unit
[0167] 100 mg of solid electrolyte B prepared by the above steps was pressurized in a cylinder made of MACOR (glass ceramic) with a diameter of 10 mm. 20 mg of positive electrode composite material powder was put into the pressurized surface and pressurized again. 20 mg of positive electrode composite material powder was put into the pressurized surface opposite to the positive electrode composite material and pressurized to prepare an ion resistance measurement unit.
[0168] Ionic resistance measurement
[0169] Using the ion resistance measurement cell produced by the above steps, AC impedance measurement was performed under the following conditions.
[0170] Frequency range: 1MHz-1mHz
[0171] Amplitude: 10mV
[0172] Table 1 shows the half width of the diffraction peak A and the left-right asymmetry parameter ε' of the diffraction peak B, as well as the ionic resistance of each composite material. Figure 1 The XRD spectrum is shown. Figure 2 An enlarged view of the high-angle side in the XRD spectrum is shown.
[0173] [Table 1]
[0174]
[0175] 3. Evaluation
[0176] As can be seen from Table 1, the positive electrode composite materials of Examples 1 to 4 have larger half widths of diffraction peak A and left-right asymmetry parameters ε′ of diffraction peak B and lower ion resistances than those of Comparative Example 1.
[0177] Depend on Figure 1It is known that the crystallinity of the solid electrolyte decreases due to mechanical mixing (for example, this can be seen from the comparison between Ref. in which mechanical mixing was not performed and Comparative Example 1 in which mechanical mixing was performed). In contrast, in Examples 1 to 4 in which a heat treatment at 160 to 220°C was performed after mechanical mixing, a peak was shown at the same position as Ref., and the crystallinity was confirmed. On the other hand, in Comparative Example 2 heated to 300°C, the peak at the same position as Ref. became smaller, and it can be considered that the solid electrolyte was decomposed (instead, the generation of an impurity phase (2θ=29°) could be confirmed).
[0178] In Examples 1 to 4, the half width of the diffraction peak A is large. Figure 2 As shown in FIG. 1 , the diffraction peak B is left-right asymmetric (the left-right asymmetry parameter ε' is large), which indicates that the solid electrolyte has generated a new crystal phase with a slightly different lattice constant in addition to the original crystal phase (such a small lattice constant and the difference in the peak position in the XRD spectrum are Figure 2 It is believed that such a feature contributes to the reduction of ionic resistance.
[0179] In addition, the results of XRD measurement of the positive electrode composite material obtained in Example 3 under the same conditions as those in Patent Document 3 are shown in Figure 3 .Depend on Figure 3 It can be seen that the behavior (split mode) of the crystal peak of the positive electrode composite material obtained in Example 3 is similar to that of the positive electrode composite material described in Patent Document 3 ( Figure 1 The XRD spectra of the embodiments are obviously different, and the crystal phases are different (it can be considered that the same is true for other embodiments).
[0180] Industrial Applicability
[0181] The positive electrode composite material of the present invention is preferably used as a positive electrode of a lithium ion battery. In addition, the lithium ion battery of the present invention can be preferably used, for example, in batteries used in information-related equipment or communication equipment such as personal computers, cameras and mobile phones, and vehicles such as electric cars.
[0182] The above-mentioned several embodiments and / or examples of the present invention have been described in detail, but it is easy for those skilled in the art to add many changes to these illustrative embodiments and / or examples without departing from the novel teachings and effects of the present invention. Therefore, these many changes are also included in the scope of the present invention.
[0183] The contents of all the documents described in this specification and the applications serving as the basis for the priority claim based on the Paris Convention of the present application are cited.
Claims
1. A positive electrode composite material, characterized in that: Contains sulfur active material and solid electrolyte, In powder X-ray diffraction using CuKα rays, there is a diffraction peak A at 2θ=25.6±0.5° and a diffraction peak B at 2θ=45.2±1.0°. The half width of the diffraction peak A is greater than 0.25°.
2. The positive electrode composite material according to claim 1, characterized in that The left-right asymmetry parameter ε' of the diffraction peak B is 1.50×10 4 above.
3. The positive electrode composite material according to claim 1 or 2, characterized in that: Also contains a conductive additive.
4. The positive electrode composite material according to claim 3, characterized in that: The conductive auxiliary agent has pores with a pore diameter of less than 5 nm.
5. The positive electrode composite material according to claim 3 or 4, characterized in that: The conductive auxiliary agent includes one or more selected from the group consisting of activated carbon and carbon black.
6. The positive electrode composite material according to any one of claims 1 to 5, characterized in that: The cathode composite material precursor is obtained by heating a sulfur-based active material and a solid electrolyte mechanically mixed, wherein the solid electrolyte has a diffraction peak A at 2θ=25.6±0.5° and a diffraction peak B at 2θ=45.2±1.0° in powder X-ray diffraction using CuKα rays.
7. The positive electrode composite material according to claim 6, characterized in that: The temperature of the heating treatment is 160-280°C.
8. A method for producing a positive electrode composite material, characterized in that: include: A positive electrode composite material precursor is obtained by mechanically mixing a sulfur-based active material with a solid electrolyte, wherein the solid electrolyte has a diffraction peak A at 2θ=25.6±0.5° and a diffraction peak B at 2θ=45.2±1.0° in powder X-ray diffraction using CuKα rays; and The positive electrode composite material precursor is subjected to a heating treatment to obtain a positive electrode composite material, The temperature of the heating treatment is 160-280°C.
9. A lithium ion battery, characterized in that: A positive electrode composite material comprising the positive electrode composite material according to any one of claims 1 to 7.
Citation Information
Patent Citations
Positive electrode mixture
JP2014011033A
Sulfur positive electrode mixture and manufacturing method thereof, sulfur positive electrode, and lithium-sulfur solid-state battery
JP2020161288A
Sulfide solid electrolyte and method for manufacturing same
WO2022080435A1